Stability of equilibrium outcomes under deferred acceptance: Acyclicity and dropping strategies - Benjamín Tello (Banco de México, 2018)
We consider the problem of matching a set of medical students to a set of medical residency positions (hospitals) under the assumption that hospitals' preferences over groups of students are responsive. In this context, we study the preference revelation game induced by the student proposing deferred acceptance mechanism. We show that the acyclicity of the hospitals' preference profile (Romero-Medina and Triossi, 2013a) is a necessary and sufficient condition to ensure that the outcome of every Nash equilibrium in which each hospital plays a dropping strategy is stable.
Keywords: C78; D47; 330; matching; stability; acyclicity; dropping strategies; Nash equilibria